Comparative Analysis of the Flavonoid Characteristics of Camellia oleifera Flowers in Different Plantations in Guizhou, China - Yurui Hao; Guandi He; Sanwei Yang; Zhannan Yang; Wenxuan Quan (BioResources)
Camellia oleifera is a multipurpose plant resource that contains flavonoids. To explore the differences in the characteristics and metabolic pathways of flavonoids in Camellia oleifera flowers from different plantations, this study compared the differences in the water content, total ash content, ethanol soluble extract, and total flavonoid content of samples from six plantations. Widely targeted flavonoid metabolomics techniques were used to analyze the metabolic characteristics of the different plantations. There were significant differences in total flavonoid content among the different plantations (P < 0.05), with Tianzhu County having the highest total flavonoid content (average value of 13.60 mg/g) and Liping County having the lowest total flavonoid content (average value of 2.39 mg/g). UPLC-MS/MS revealed a total of 13 categories and 758 flavonoid metabolites, among which flavonols, flavonoids, and tannins were the main flavonoid compounds. A total of 266 differentially abundant metabolites were screened via the OPLS-DA model, and KEGG enrichment analysis revealed that the enrichment pathways of differentially abundant metabolites between different plantations were related mainly to the biosynthesis of secondary metabolites, flavonoid biosynthesis, metabolic pathways, etc. This study provides a theoretical reference for the subsequent development and utilization of Camellia oleifera resources, especially in the utilization of Camellia oleifera flower resources.